Program Pembinaan di Lapas Kelas II B Lamongan Perspektif Filsafat Hukum Pidana Islam - Aprilianto, Dwi (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2015)
Within Islamic philosophy, the implementation of punishment for those who commit a crime (jarÃ®mah) is a form of prevention and retaliation (al-radâ wa al-zajr) as well as correction and education (al-islÃ¢h wa al-tahdhÃ®b). The implementation of imprisonment in Islam is categorized as taâzÃ®r, since there is no any stipulation in the Qurâan which regulates about imprisonment. Departing from this paradigm, this study concludes that the implementation of punishment in the form of imprisonment corresponds with the aim of punishment itself within Islamic criminal laws. However, the writer argues that the implementation of imprisonment in Indonesia should be seriously enforced in order to obtain its main objective. This is because the society tends to put a negative stigma upon those who have imprisoned. Therefore, the government, penitentiary officers, and the society should work together to help and educate the convicts. Moreover, the government should be responsible for providing the penitentiary adequate facilities to support the process of education and its effectiveness